2012
DOI: 10.1177/0959683612449762
|View full text |Cite
|
Sign up to set email alerts
|

Application and limitations of the Artemisia/Chenopodiaceae pollen ratio in arid and semi-arid China

Abstract: The Artemisia/Chenopodiaceae (A/C) ratio is assumed to be a useful index for reconstructing moisture changes in arid and semi-arid regions. Thorough modern pollen studies are still lacking to understand the reliability and limitation of A/C ratio as a moisture indicator, however. Here we review how well this ratio can be applied in arid and semi-arid China on the basis of new surface pollen data, previous data synthesis and other publications. Results indicate that variance in the A/C ratio can permit identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 23 publications
5
72
0
Order By: Relevance
“…1a), and further data collection is still required. More recent collection of modern pollen data at regional scales, such as on the Tibetan Plateau (Lu et al, 2011;Zhang et al, 2012), arid and semi-arid northern to western China (Zhao et al, 2012), the South China Sea (Luo et al, 2013), and throughout China (Zheng et al, 2010), are not or not wholly included in our dataset. However, fossil pollen data are necessary and required for more unambiguous reconstruction of biome boundaries, especially in central eastern China between temperate and warm-temperate (subtropical) forest biomes and in central western China between temperate desert and alpine tundra biomes (Fig.…”
Section: Quality Of Pollen Data Used In This Studymentioning
confidence: 99%
“…1a), and further data collection is still required. More recent collection of modern pollen data at regional scales, such as on the Tibetan Plateau (Lu et al, 2011;Zhang et al, 2012), arid and semi-arid northern to western China (Zhao et al, 2012), the South China Sea (Luo et al, 2013), and throughout China (Zheng et al, 2010), are not or not wholly included in our dataset. However, fossil pollen data are necessary and required for more unambiguous reconstruction of biome boundaries, especially in central eastern China between temperate and warm-temperate (subtropical) forest biomes and in central western China between temperate desert and alpine tundra biomes (Fig.…”
Section: Quality Of Pollen Data Used In This Studymentioning
confidence: 99%
“…Previous studies in the drylands of the Middle East (El-Moslimany 1990) have demonstrated that Chenopodiaceae are indicators of saline or non-saline desert vegetation, whereas Artemisia pollen generally increases with increasing MAP. Thus, the ratio of these two taxa has been used as an index for moisture regimes Liu et al 1999;Li et al 2005;Zhao et al , 2012. In our study, the A/C ratio was calculated to understand the response of this ratio to changes in MAP within vegetation zones in the study area and to determine if the A/C ratio can be used for semiquantitative palaeoclimate reconstructions.…”
Section: Numerical Analysismentioning
confidence: 99%
“…Recently, Zhao et al (2012b) reviewed the reliability of the A/C ratio as humidity indicator in the arid region of China. They suggested that the A/C ratio can only be used to evaluate the humidity variations in regions with precipitation <450-500 mm, and environmental factors such as soil salinity, vegetation community composition, and human activity can also affect the validity of the A/C ratio.…”
Section: Pollen Ratios Vegetation and Climatementioning
confidence: 99%